Republic of Armenia : Second Reviews Under the Extended Fund Facility and Extended Credit Facility, and Request for Modification of Performance Criteria; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Armenia. (IMF Staff Country Reports; Country Report, 2011)
In this study, Armenia's financial challenges observed in the global crisis are discussed, and also the development processes initiated by Armenia are analyzed. Short- and medium-term outlooks, and risks are also outlined. Fiscal, monetary, and banking sector policies play important roles in the development of the financial system. Structural reforms are accelerated for addressing imbalances, sustainable growth, and poverty reduction. Sound macroeconomic policies and structural reforms will help to ensure rise in productivity, exports, and inflation pickup and reduce the foreign exchange risk.